Career transitions: actionable recommendations by graduate students and postdoctoral scholars on achieving research independence in biomedical sciences - Singh, Harinder; Bankston, Adriana; McDowell, Gary S. (Frontiers in Education, 2025)
Academic research in the U.S. is managed through and driven by principal investigators overseeing independent research programs, often with a goal of training researchers in the process. The theoretical path to becoming a principal research investigator consists of developing research skills during a PhD, followed by “apprentice”-style research experiences as a postdoctoral researcher, ultimately leading to independent leadership of research projects (and teams) as a faculty member. Early career researchers looking to climb this career ladder therefore need to develop research “independence”, or independence of thought. Workshops conducted with graduate students and postdoctoral researchers in biomedical sciences at multiple universities revealed barriers to research independence. Through these workshops, early career researchers identified solutions to achieving research independence, which revolve around intellectual contributions, training and mentorship, career development and progression, compensation and benefits, work-life balance and mental health, and finally immigration and visas. We propose that systemic changes in these areas will lead to the development of a healthy and productive research enterprise that can build future leaders in the field through developing independent researchers who can advance scientific research.